Convergence: A key for scaling innovation into impact - Munshi, Sugandha; Kumar, Virender; Malik, R.K. (International Rice Research Institute, 2023)
Farmers across the regions face challenges due to climate change. When the challenge is big, solution and innovation designs need to come together away from the silos.